PERANAN BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH DALAM MENGOPTIMALKAN PENERIMAAN PAJAK BUMI DAN BANGUNAN DI KABUPATEN MUARO JAMBI - Hermayanti Hermayanti; Cynthia Andari (Universitas Batanghari Jambi, 2017)
Since the establishment of the regulatory region number 8 year 2012 about Earth and Rural Building Tax, tax on the Earth and the building became one of the original sources of income sufficient potential areas in order to finance the holding of local governance in the County Muaro Jambi. Implementation of a new beginning in 2013 which was carried out by the regions in the field regional financial management, namely Management of taxes and Regional Levies (BPPRD). BPPRD is claimed to be capable of playing its role optimally considering tax on Earth and it has a scope object of the tax is quite extensive, so it is expected to reach the target of acceptance has been set. This study is an empirical approach to legal research socio legalresearch, describes the role of BPPRD in optimizing the tax receipts of the Earth and buildings as well as the efforts undertaken in optimizing a tax receipt BPPRD of the Earth and buildings in Muaro Jambi Regency. Sejauhmana BPPRD is able to optimize the role of measured based on the percentage of successful acceptance realized from a predetermined target, in this case 2013-2016 year. Based on the percentage to be visible tendencies are appropriate benchmarks that have been set previously. The results showed that at the beginning of the execution of the year 2013, the role of the BPPRD walking less than optimal, then from the year 2014 to 2016 the role of highly optimized BPPRD. As for the efforts done BPPRD Muaro Jambi Regency is by doing a variety of efforts, good efforts of ektensifikasi and intensification of tax.Keywords: Role, BPPRD Muaro Jambi Regency, Optimal, Earth and building tax receipt